Pemberdayaan Masyarakat Dalam Realisasi Budidaya Ikan Lele Di Desa Lembengan Kabupaten Jember - Sumarya, Erdin Handika; Natus, Angelique Salsabillah Yumna Patricia; Salsabil, Shofy; Lesanti, Putri; Atasa, Dita; Megasari, Dita (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract The Community Service Program (KKN) in Lembengan Village, Jember Regency, focuses on cultivating catfish as a strategic step to increase food security and reduce stunting rates in the community. The choice of this topic was based on the high prevalence of stunting and nutritional problems in the village. The methods used include collaboration between KKN students, village officials, the Village Children's Forum (FAD), and the Jember District Fisheries Service. Core activities include distributing catfish seeds, raising awareness about cultivation, and education about the benefits of consuming catfish for pregnant women and children. The results of the activity showed a positive response from the community and village officials, with indications of increased awareness of the importance of nutrition and the economic potential of catfish cultivation. This program also produces a Follow-up Plan (RTL) which will be continued by the Village Children's Forum to ensure the sustainability of catfish cultivation in Lembengan Village. In conclusion, this initiative has great potential to improve community welfare and provide a positive long-term impact. Keywords: Catfish Cultivation, Nutrition for Pregnant Women and Children, Food Security, KKN, Stunting